Establishing the minimal clinically important difference of the 6-min walk test in lung transplant recipients undergoing pulmonary rehabilitation: a prospective analysis - Wang, Peijian; Gao, Beiyao; Sun, Jing; Yu, Yang; Ge, Lijun; Chen, Wenhui; Jiang, Shan; Wang, Siyuan (Frontiers in Medicine, 2026)
PurposeThis study aimed to evaluate the responsiveness of the 6-min walk test (6MWT) to pulmonary rehabilitation (PR) in lung transplant recipients (LTRs) and to establish the minimum clinically important difference (MCID) for the 6MWT in this population.Materials and methodsEighty-one LTRs from a single-center randomized controlled trial were included. The MCID was calculated using anchor-based (handgrip strength) and distribution-based methods. Handgrip strength (left, right, and average) and 6MWT distance were assessed before and after an 8-week PR program.ResultsAll 81 participants completed PR. The 6MWT distance improved significantly, with a mean change of 73.37 m (Cohen’s d = 1.10). Handgrip strength increased by 7.24–8.21 kg (Cohen’s d = 0.80–0.91; all p < 0.001). Changes in handgrip strength were strongly correlated with changes in 6MWT distance (r = 0.63–0.69; p < 0.001). The MCID was estimated at 52.65–58.5 m (anchor-based), 57.28–59.40 m (distribution-based), and 56.83 m (combined).ConclusionThe 6MWT is responsive to PR in LTRs. A MCID of 56.83 m provides a clinically meaningful benchmark for interpreting exercise capacity changes and can guide sample size estimation in future trials.